2015
DOI: 10.1155/2015/349070
|View full text |Cite
|
Sign up to set email alerts
|

MixedLpEstimators Variety for Model Order Reduction in Control Oriented System Identification

Abstract: A new family of MLE typeLpestimators for model order reduction in dynamical systems identification is presented in this paper. A family ofLpdistributions proposed in this work combinesLp2(1<p2<2) andLp1(0<p1<1) distributions which are quantified by four parameters. The main purpose is to show that these parameters add degrees of freedom (DOF) in the estimation criterion and reduce the estimated model complexity. Convergence consistency properties of the estimator are analysed and the model order re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(45 reference statements)
0
2
0
Order By: Relevance
“…Indeed, this remains in agreement with the formal point of view related to the bias and the new curve in Section 2.3: low values of γ involve reduced bias and improve the FIT of the reduced order model. In Corbier and Carmona [13] we showed that the Huberian model order denoted d…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Indeed, this remains in agreement with the formal point of view related to the bias and the new curve in Section 2.3: low values of γ involve reduced bias and improve the FIT of the reduced order model. In Corbier and Carmona [13] we showed that the Huberian model order denoted d…”
Section: Resultsmentioning
confidence: 93%
“…However, it remains to characterize more appreciably the diseases to differentiate the neurodegenerative disorders. Accordingly, future work will focus on mixed L p estimator [13] to reduce the number of parameters providing new indicators and will investigate the memory effect of human walking.…”
Section: Resultsmentioning
confidence: 99%